A Characteristic Investigation of Aminocyclohexane-N′-methylurea as a Corrosion Inhibitor for Mild Steel in 1 N H2SO4. (13th September 2012) - Thiraviyam, P.; Kannan, K.; Premkumar, P.
Abstract : The newly synthesized aminocyclohexane-N′-methylurea Mannich base was characterised using FT-IR, H 1 NMR, and C 13 NMR spectra and also it was tested as corrosion inhibitor for the mild steel in 1 N sulphuric acid. Inhibitive study of this compound was carried out by weight loss method over the temperature range of 303–333 K, potentiodynamic polarisation, and AC impedance methods. The inhibition efficiency was increased with increasing concentration of inhibitor whereas it was decreased with increasing temperature. Potentiodynamic polarisation study showed that ACMU is a mixed type inhibitor. AC Impedance study reveals that the corrosion of steel was mainly controlled by a charge transfer process. Surface analysis was carried out using SEM technique. The adsorption of inhibitor follows the Tempkin and Langmuir adsorption isotherms. The activation energy ( E a ), free energy change (Δ G ads ), enthalpy change (Δ H ads ) and entropy change (Δ S ads ) were calculated to understand the corrosion inhibition mechanism.